Efficient catalytic As(III) oxidation on the surface of ferrihydrite in the presence of aqueous Mn(II). (1st January 2018) - Lan, Shuai; Ying, Hong; Wang, Xiaoming; Liu, Fan; Tan, Wenfeng; Huang, Qiaoyun; Zhang, Jing; Feng, Xionghan
Abstract: Arsenic is a carcinogenic element that exists primarily as arsenate [As(V)] and arsenite [As(III)] in the nature environment, with As(III) being more toxic and mobile of the two species. In addition, ferrihydrite, which is widely distributed in soils and aquatic environments, can catalyze the oxidation of Mn(II) and accelerate the formation of high-valence Mn, which can significantly influence the speciation, toxicity, and mobility of As when these species co-exist. In this context, we herein explored the mechanism of As(III) oxidation in the presence of ferrihydrite and Mn(II) using a kinetic approach combined with multiple spectroscopic techniques, including X-ray absorption near edge spectroscopy, in situ horizontal attenuated total-reflectance Fourier transform infrared spectroscopy, and in situ quick scanning X-ray absorption spectroscopy. Our results indicate that efficient As(III) oxidation by dissolved O2 occurs on the surface of ferrihydrite in the presence of aqueous Mn(II). Compared with As(III) oxidation in the presence of ferrihydrite and Mn oxides ( i.e., Mn oxides/hydroxides), the degree of As(III) oxidation in the ferrihydrite-Mn(II) system was significantly higher, and the majority of generated As(V) was adsorbed on the mineral ( i.e., ferrihydrite) surface. Furthermore, As(III) oxidation was enhanced upon increasing both the molar ratio of Mn(II)/As(III) and the solution pH. The greater As(III) oxidation by O2 in the ferrihydrite-Mn(II) system was mainly attributed to the formation of a strong oxidant of the instantaneous intermediate Mn(III) species via Mn(II) oxidation under catalysis by the ferrihydrite surface. Moreover, As(III) oxidation occurred mainly on the ferrihydrite surface and was accompanied by the regeneration of Mn(II), thereby rendering it recyclable. These results therefore provide new insights into the mechanism of As(III) oxidation on the surfaces of Fe oxides ( i.e., Fe oxides/hydroxides) in the presence of aqueous Mn(II) as well as the new details regarding the electron transfer mechanisms between the As(III)-Mn(II, III)-O2 species at the ferrihydrite surface, and could lead to novel approaches for As(III) contaminant remediation in the environment. Graphical abstract: Image 1 Highlights: Efficient As(III) oxidation and immobilization occur on ferrihydrite with aqueous Mn(II). As(III) oxidation is enhanced with increasing both Mn(II)/As(III) molar ratio and pH. Coupling processes between Mn(II) and As(III) oxygenation on ferrihydrite are elucidated. Ligand-free Mn(III) intermediate species acts as the main reactive oxidant for As(III) oxidation. The regeneration of Mn(II) during As(III) oxidation renders it recyclable and little consumed.